"My little piece of the planet": the multiplicity of well-being benefits from allotment gardening. Issue 3 (3rd November 2020) - Dobson, Miriam Clare; Reynolds, Christian; Warren, Philip H.; Edmondson, Jill L.
Abstract : Purpose: Participation in urban horticulture (UH) is increasing in popularity, and evidence is emerging about the wide range of social and environmental benefits "grow your own" can also provide. UH can increase mental and physical well-being, as well as improve nature connectedness, social capital and community cohesion. Design/methodology/approach: This study focusses on allotments, which is one of the dominant forms of UH that takes place in the United Kingdom. 163 volunteers in England and Wales participated in keeping a year-long allotment diary as part of a citizen science project investigating activities on allotment gardens. This study examines the unprompted comments that 96 of these gardeners offered as observations when visiting their allotment plots. Findings: Participants recorded high levels of social and community activities including the sharing of surplus food produce, knowledge exchange, awareness and interaction with wildlife, emotional connection to their allotment, appreciation of time spent outside and aesthetic delight in the natural world around them. Originality/value: At a time when waiting lists for allotment plots in the United Kingdom are on the rise, and allotment land is subject to multiple pressures from other forms of development, this study demonstrates that these spaces are important sites not only for food production but also health, social capital and environmental engagement.